Wireless positioning methods for mitigating the influence of environmental and terminal diversity - Jietai WANG; Youlian GUAN; Xiaoniu YANG; Zhenxing LUO; Jianbiao YU (Dianxin kexue)
Two optimization algorithms respectively were proposed according to the traditional two methods based on ranging and fingerprint-based to mitigate or circumvents the influence of environmental parameters on the position-ing results and compared traditional benchmark algorithms and recent similar work through simulation and actual scene experiments.The experimental results show the effectiveness of the algorithms:compared with the traditional benchmark algorithms,the positioning accuracy is improved by about 70%,compared with the recent similar work,the positioning accuracy is also improved by about 20%,at the same time,the change of the environmental parame-ters has little impact on the stability of the proposed algorithm.